The Asia-Pacific in the age of transnational mobility : the search for community and identity on and through social media - Gomes, Catherine Jean (London : Anthem Press, 2016)
The growing mobility of people within and into the Asia Pacific region has created environments of increasing diversity as nations become hosts to both permanent and temporary multicultural societies. As individuals and groups navigate through an increasingly mobile, transnational and multicultural ethnographic landscape, social media provides a sense of belonging for these networked communities. This book is a study of the challenges of community and identity in the evolving transnational migrant and ethnographic landscapes of the Asia Pacific in the era of social media.
Female Indonesian migrant domestic workers in Hong Kong : a case study of advocacy through Facebook and the story of Erwiana Sulistyaningsih / Panizza Allmark and Irfan Wahyudi -- Media and mobilities in Australia : a case study of Southeast Asian international students' media use for well-being / Larissa Hjorth and Joshua Wong -- Connecting and re-connecting with Vietnam : migration, Vietnamese overseas communities and social media / Cate Gribble and Ly Thi Tran -- Liking it, not loving it : international students in Singapore and their navigation of everyday life in transience / Catherine Gomes -- Is "Allah just for Muslims"? : religion, indigenization and boundaries in Malaysia / Susan Leong -- Ethnic minorities in the multi-ethnic heritage in Melaka : reconstructing Dutch Eurasian and Chitty Melaka identites through Facebook / Loo Hong-Chuang and Floris Müller -- Nostalgia and memory : remembering the Malayan communist revolution in the online age / Jason Sze-Chieh Ng -- New and traditional media in Malaysia : conflicting choices for seeeking useful and trusted information in everyday life / Sandra Harchard.
Title from publisher's bibliographic system (viewed on 11 Aug 2017).
Keywords: Online social networks -- Asia -- Case studies; Online social networks -- Pacific Area -- Case studies; Social media -- Asia -- Case studies; Social media -- Pacific Area -- Case studies; Transnationalism -- Social aspects -- Asia -- Case studies; Transnationalism -- Social aspects -- Pacific Area -- Case studies